Localised oral amyloidosis in the context of oral epithelial dysplasia: Literature review and report of two cases. (3rd May 2021) - Dobson, Marianne L.; Wright, Alison L.; White, Sharon J.; Macluskey, Michaelina
Abstract: Amyloidosis is a group of rare progressive diseases that occur as a result of abnormal protein folding and aggregation. Systemic amyloidosis is a serious disease with high mortality, and prompt diagnosis is key to improving prognosis. Conversely, localised amyloidosis does not reduce life expectancy and can often be treated with simple surgical excision. Amyloid deposits can be found in the oral cavity, usually in the context of systemic amyloidosis. We present two cases of localised oral acquired immunoglobulin light chain (AL) amyloidosis that were detected in oral biopsies taken for the management of oral epithelial dysplasia (OED). Both patients underwent thorough multisystem investigations by haematology in conjunction with the NHS National Amyloidosis Centre (NAC) in order to exclude systemic amyloidosis and confirm the diagnosis. Localised oral amyloidosis is rare, and to our knowledge, localised oral AL amyloidosis has not been reported in the context of OED before. We discuss important learning points from these cases as well as hypothesising on the pathophysiology involved.